GR_GERICHTE ZF 2005 16 vom 7. Juli 2005 , Rechenschaftspflicht/Forderung - GR Gerichte (2005)
Forderung | Leitentscheid, publiziert als PKG 2006 4\x3Cbr\x3E | OR Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc. (OR 394-529)